2009
DOI: 10.1007/s11259-009-9335-z
|View full text |Cite
|
Sign up to set email alerts
|

Designing and evaluation of sodium selenite nanoparticles in vitro to improve selenium absorption in ruminants

Abstract: Sodium selenite is used to prevent selenium deficiency known as nutritional muscular dystrophy or white muscle disease. In ruminants, selenium supplements are transformed partiality in insoluble form by ruminal microorganisms and its process decrease the selenium absorption in digestive gastrointestinal. However, the objective in this research was focused in encapsulated sodium selenite to be release into of a pH less than four, similarity to an intestinal environment. It was encapsulated by nanoprecipitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 11 publications
2
45
0
2
Order By: Relevance
“…reported that nanotechnology has the potential to change the particles of materials from a large scale to nano-scale particles (1 to 300 nanometers in size). At this small size the properties and characteristics can differ considerably with particles of larger sizes [13]. Unfortunately there is a lack or even null information regarding the use of nanotechnology in broiler feeding and nutrition.…”
Section: Carcass Characteristicsmentioning
confidence: 99%
“…reported that nanotechnology has the potential to change the particles of materials from a large scale to nano-scale particles (1 to 300 nanometers in size). At this small size the properties and characteristics can differ considerably with particles of larger sizes [13]. Unfortunately there is a lack or even null information regarding the use of nanotechnology in broiler feeding and nutrition.…”
Section: Carcass Characteristicsmentioning
confidence: 99%
“…This is because nanotechnology has the potential to change the particles of material from large scale to nanoscale generally 1-300 nm in size [15]. At this small size, the properties and characteristics can differ considerably compared to those at large scales [16]. Unfortunately, there is a lack or null information about the use of nanotechnology in poultry production particularly broiler feeding.…”
Section: Discussionmentioning
confidence: 99%
“…However, we believe that the chemical composition of aqueous nanosuspension that contains mineral elements plays a role in improving antibodies production noticed in the present study. In this regard, it has been reported that minerals are one of the most widely supplements used in poultry and animal nutrition [16]. Additionally, the way in which minerals are found influences their bioavailability, and so far, if they have low bioavailability, the animal will not make suitable use of them.…”
Section: Discussionmentioning
confidence: 99%
“…insoluble form by microorganisms in ruminant's body, and its process decreases the selenium absorption in the digestive gastrointestinal cavity [25]. Selenium occurs in multiple oxidation states, for example, +6, +4, 0, or −2 [12].…”
Section: Kumar and Prasadmentioning
confidence: 99%